Review: recent developments in 2D MXene-filled bioinspired composites for biomedical applications - Akinay, Yuksel; Topuz, Mehmet; Gunes, Umit; Gokdemir, Muhammet Enver; Cetin, Tayfun (SPRINGER, 2025)
Two-dimensional carbide- and nitride-based MXene materials have become some of the most studied materials in interdisciplinary fields due to their superior properties. This review comprehensively discusses recent advances in MXene materials such as bioinspired coating films, scaffolds, and electrochemical activities for use in biomedical fields. MXene consists of multilayer 2D nitride, carbide, or carbonitride flakes with excellent electrical conductivity, large surface area, and good mechanical properties. Bibliometric studies have revealed a sharp increase in the number of publications and citations, having reached 15,831 records as of February 2025. Notably, the number of citations surged from under 20 in 2012 to over 222,000 in 2024. Due to being two-dimensional materials with superior physicochemical and biological properties, MXenes are also being increasingly used in biomedical and engineering applications. They have been reported to be ideal for such biomedical applications as corrosion-resistant biofilms, biocompatibility, low toxicity, drug delivery, and tissue engineering. In addition, MXene-based scaffolds have emerged as a promising material for bone tissue engineering due to their extraordinary mechanical durability, biocompatibility, and adjustable surface properties. By aiding tissue regeneration and preventing infections, MXene scaffolds have also been found to exhibit enhanced drug delivery and antibacterial properties. Recent advances in materials science have focused on creating bioinspired structures with multifunctionality. Taking into account MXenes' multilayered structures and functional surfaces, unique physicochemical properties have been designed by learning from nature to produce bioinspired materials. This article comprehensively reviews biomedical applications of such 2D MXene materials as bioinspired coating films, scaffolds as biosensors, drug delivery, cancer treatments, and tissue regeneration.
Keywords: TRANSITION-METAL CARBIDES; SCAFFOLDS; HYDROGEL; FABRICATION; SYSTEMS; DESIGN; SKIN; Materials Science